2019
DOI: 10.23960/mech.v10.i1.201905
|View full text |Cite
|
Sign up to set email alerts
|

Simulasi Unjuk Kerja Termal Dan Pressure Drop Kolektor Surya Pelat Datar Aliran Serpentine Menggunakan Metode CFD

Abstract: Untuk mengetahui karakteristik unjuk kerja kolektor surya ini dapat digunakan metode CFD (Computational Fluid Dynamic). CFD memberikan kemudahan untuk menganalisis karakterisrik aliran fluida yang berkaitan dengan distribusi temperatur dan tekanan yang terjadi. Tujuan penelitian ini adalah menganalisis karakteristik unjuk kerja termal dan pressure drop pada kolektor surya pelat datar menggunakan metode CFD. Langkah-langkah yang dibutuhkan dalam proses simulasi CFD adalah: desain dan name selection geometri, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…5. Results and Discussion Previous research [16] Ansys software validation has been carried out by comparing the results of simulation tests with experimental data, it is found that there is a closeness of the correction factor values which tend to be the same between the simulation results and the experimental data. Thus, the simulation software used can be relied upon to predict the thermal characteristics of the collector.…”
Section: 4mentioning
confidence: 93%
“…5. Results and Discussion Previous research [16] Ansys software validation has been carried out by comparing the results of simulation tests with experimental data, it is found that there is a closeness of the correction factor values which tend to be the same between the simulation results and the experimental data. Thus, the simulation software used can be relied upon to predict the thermal characteristics of the collector.…”
Section: 4mentioning
confidence: 93%
“…Berdasarkan penelitian dari [8], yang memelakukan penelitian dengan simulasi CFD tentang kolektor surya pelat datar menggunakan pipa sebagai tempat aliran fluida kerja, simulasi dipilih untuk menngurangi biaya pembuatan variasi kolektor. Dari penelitian tersebut terdapat dua bentuk pipa yang dibahas yaitu bentuk pipa serpentine dan spiral.…”
Section: Pendahuluanunclassified
“…It can be analyzed to characterize its thermal performance and pressure drop using the Computational Fluid Dynamic (CFD) simulation method. From this basis, research on the use of solar energy is needed to support the use of new and renewable energy (EBT) [6].…”
Section: Introductionmentioning
confidence: 99%